On-Premise Alcohol Establishments and Ambulance Calls for Trauma, Assault, and Intoxication. Issue 19 (May 2016) - Ray, Joel G.; Turner, Linda; Gozdyra, Piotr; Matheson, Flora I.; Robert, Burgess; Bartsch, Emily; Park, Alison L.
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Alcohol contributes to intentional and unintentional injury. We explored on-premise licensed alcohol establishments (LAEs) and emergency medical service (EMS) ambulance calls. We completed a retrospective population-based study in the Region of Peel, Ontario, 2005 to 2014, where alcohol sales are tightly regulated and healthcare is universally available. We included participants age ≥ 19 years. Longitude–latitude coordinates of all 696 LAEs and all 267, 477 EMS ambulance calls were ascertained, and then assigned to 1 of 1568 dissemination areas (DA) in Peel. Relative risks (RRs) described the association between density of on-premise LAEs (by DA deciles) and the rate of EMS calls, adjusted for material deprivation, and density of beer/liquor stores in each DA. There was a curvilinear relation between LAE density and EMS calls for trauma, rising from 45.3 per 1000 in DAs with no LAEs to 381.0 per 1000 in decile-10 (adjusted RR 7.83, 95% confidence interval [CI] 6.15–9.97). This relation was more pronounced for alcohol-focused LAEs, and highest among younger males. Calls for assault (RR 2.67, 95% CI 1.26–5.65) and intoxication (RR 4.00, 95% CI 1.41–11.38) were more likely on the last day of the month and the day thereafter, compared to 1 week prior. At 02:00 hours, when LAEs must stop selling alcohol, there was a considerable rise in assault-related calls in DAs with LAE but not in DAs without LAEs. On-premise LAEs contribute to EMS calls for trauma and assault, especially among young males, around last call, and when monthly pay cheques are cashed.